1988
DOI: 10.1177/002248718803900403
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Feedback Approaches for Improving Student Teachers' Classroom Instruction

Abstract: Freiberg and Waxman describe three approaches for providing feedback that have not been widely used but have great potential for improving the classroom instruction of preservice teachers.The methods include: (a) feedback from pupils, (b) systematic feedback from classroom observation systems, and (c) self-analysis of classroom lessons. The authors argue that these feedback approaches, individually or collectively, provide student teachers, cooperating teachers, and university supervisors with excellent data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Moreover, teachers appreciate the feedback they receive after a walkthrough observation or a formal observation as an effective avenue to enhance their own development (Ovando, 2001). Others also support the value of written feedback as a mechanism to influence teachers' instructional behaviors (Freiberg & Waxman, 1988).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, teachers appreciate the feedback they receive after a walkthrough observation or a formal observation as an effective avenue to enhance their own development (Ovando, 2001). Others also support the value of written feedback as a mechanism to influence teachers' instructional behaviors (Freiberg & Waxman, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that written feedback from principals, mentors, coaches and others has potential to influence teachers' instructional behaviors (Freiberg & Waxman, 1988). Supporting the potential of supervisory feedback for professional development purposes, Kochan & Trimble (2000) agree that "understanding new concepts and adapting behaviors to operate effectively in new work environments requires practice, feedback and reflection" (p. 20).…”
Section: Constructive Feedbackmentioning
confidence: 99%
“…The videotapes were reviewed and analyzed using both the quantitative and qualitative methods. A Teacher Observation Schedule, adapted from Stallings Observation System (Freiberg and Waxman, 1988;Stallings, 1986) was used to quantify the number of instructional activities and teacherstudent interactions in the classroom. Three members of the research team coded the occurrences of different types of instructional activities and teacher-student interactions at the frequency of two times each five minutes.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, whenever any pupil gives a imprecise answer, the teacher needs to correct the answers immediately and thus create pupils' creativity (Salvin, 1998). Inquiry skill is a relatively important approach because it is the most commonly used technique after lecture technique in a teachers' teaching technique (Freiberg, 1988). The waiting time is classified into waiting time I and waiting time II, depending on the definition used.…”
Section: Introductionmentioning
confidence: 99%